Seasonal Growth and Instability of Ring Seine Fishery in Kerala - Dhiju Das, P. H.; Sruthi, P.; Gopal, Nikita; Edwin, Leela (Fishery Technology, 2018)
Ring seine, which is the major fishery of Kerala,contributes 55.7% of the state’s total marine fishproduction and contributes 21.31% of the totalmarine landings of the country, out of which 73.4%is of pelagic resources. Even small fluctuation in theannual output of ring seine reflects on the total fishproduction of the state. Two types of ring seinesystems are operating in Kerala, namely, mechanised(fitted with inboard motors or IBM) and motorized(operated with outboard motors or OBM). Thispaper examines the growth and instability of fishproduction from the ring seiners operating fromcentral Kerala, India during the period 2002-2011.Time series data on daily landing from 36 fishingvessels, including 27 mechanised and 9 motorizedring seine units were used for the study. The resultsreveal that there is a positive growth in theproduction from the mechanised ring seiners whilethe growth from the motorized sector has beenfalling over the period under study. The overallinstability ranged from 36-38% and was moreprominent in motorized vessels.